COVID-19 and Construction: Impact Analysis on Construction Performance during Two Infection Waves in Victoria, Australia - Bell, James; Chan, Henry; Chan, Michael; Moon, Sungkon (Sustainability (Switzerland), 2022)
This research outlines the fluctuation in confirmed active cases of coronavirus disease 2019 (COVID-19), as related to the changes in the Victoria state government’s rules and restrictions. Further, this study examines the impact of government restrictions on the performance of construction in Victoria, Australia. The data analyses in this paper identify the specific effects on industrial production, during the different lockdown stages, in three local construction companies. Companies were selected from different points along the supply chain. Company A is a supplier involved in the manufacturing of structural steel. Company B conducts logistics and procurement. Company C is a construction engineering business specializing in foundations. After reviewing relevant case studies and theories, data analyses were developed in collaboration with these companies. The results revealed that the impact of restrictions on the workers on individual construction projects was not significant. Stage 4 restrictions (Victoria’s highest lockdown level) significantly impacted overall income by limiting construction to only servicing essential infrastructure or essential businesses. The novel contribution of this study is the data analysis outcome for Victoria, where a high level of restrictions were experienced, such as curfew and enforced isolation at home, relative to other countries. In 2021 and 2022 (omicron variant dominated), Victoria was again at the brink of an infection wave, which showed a similar pattern to July 2020, and endured the world’s longest COVID-19 lockdown. The research findings contribute to the body of knowledge by providing empirical data analysis of each company, representing the economic impact of ordinary small and medium enterprises (SMEs) in construction.
Keywords: Australia; COVID-19; COVID-19 and construction; Impact analysis; Pandemic; Victoria